Desarrollo y reproducción de Bemisia tabaci "B" (Hemiptera: Aleyrodidae) sobre genotipos de yuca (Manihot esculenta) - Carabalí Muñoz, A.; Montoya Lerma, J.; Bellotti, Anthony C. (2008)
The geminiviruses of cassava mosaic virus (CMGs) (Geminiviridae, Begomovirus) and their whitefly vector, Bemisia tabaci, produce the major losses in root yield of cassava crops in Asia and Africa. Recent evidence suggests that B. tabaci represents a complex of morphologically indistinguishable populations with numerous biotypes. In the Americas, although cassava seems not to be a suitable host for the polyphagous biotype B, it has being postulated that the absence of CMGs and the mechanical damage are related with incapability of this biotype to colonize efficiently this crop. However, previous studies have demonstrated that their adaptation to cassava, via alternate hosts, is a risk that must always be kept in mind. The main objective of this study was to evaluate the development and reproduction of B. tabaci biotype B feeding on three genotypes of M. esculenta (MEcu72, CG489-34 and CMC-40). Bioassays, carried out under controlled conditions (25±2°C, 70±5RH; 12:12 LD), were used to evaluate longevity, fecundity, reproduction and demographic parameters through life tables. Although mean values for longevity were similar in MEcu72, CG489-34 and CMC-40 (6.3, 5.07, and 3.9 days, respectively) CMC-40 showed the lowest oviposition rate (0.49 eggs/female/ 2days) compared with MEcu72 (0.89) and CG489-34 (0.86). With a very low survival rate (0.03), MEcu72 was the only genotype where the biotype B was able to complete its development from egg to adult, requiring 55.1 days. Results are discussed in terms of evaluating the potential adaptation of B. tabaci on commercial cassava genotypes.